Sleep disorders in patients diagnosed with Parkinson’s disease at a specialized medical center in Rosario (Santa Fe, Argentina), 2024 - Boschi de Abreu Cavalli , Kimberly; Filippini , Fernando; Cortadi , Pablo (International Journal of Neurology, 2025)
Introduction: Sleep disorders are a common complication in patients with Parkinson’s disease (PD), significantly affecting their quality of life. Objective: To describe the frequency of sleep disorders in patients diagnosed with Parkinson’s disease at a specialized medical center in Rosario in 2024. Materials and Methods: Quantitative, observational study with a descriptive cross-sectional and retrospective design. Conducted at the Le Sommeil Sleep Disorders specialized medical center. The population consisted of all patients over 18 years of age diagnosed with PD. The instrument used for data collection was a survey specifically designed for this study, reviewed and validated by specialists. The variables were analyzed using absolute and relative percentage frequencies. Results: Seventy-one patients were analyzed; of these, 54% were male. The average age was 73.9 ± 10.9 years. The most common age group was 70–79 years. The highest number of patients diagnosed was recorded in the period 2020–2024, representing 57.7% of the total. On average, the time between the onset of symptoms and diagnosis was one year. Sixty-four point eight percent of patients had the right side as their dominant side. Sixty point six percent of patients reported tremor as the most common symptom. Insomnia was the most frequently reported sleep disorder symptom in 32.4% of patients. Tremor was the most common symptom in 64.8% of patients, with a greater presence on the right side of the body. Conclusion: The results showed a higher prevalence of the disease in older men, with symptoms such as tremor and sleep disorders such as insomnia. In addition, a greater impact was observed on the right side of the body, both in motor symptoms and sleep disorders.